Talent identification and development in sport. International perspectives (Routledge, 2021)
Identifying and developing talented athletes to their fullest potential is a central concern of sport scientists, sports coaches, and sports policy makers. The second edition of this popular text offers a state of the science synthesis of current knowledge in talent identification and development in sport, from the biological basis of talent to the systems and processes within sport through which that talent is nurtured.